A Marxist Feminist Analysis of Nafisa Rizvi’s The Blue Room - Nazash Jamal; Aziz Ahmad; Inam Ullah Mian (University of Chitral Journal of Linguistics and Literature, 2023)
The life of women in a conservative capitalist society is always pitiful. They face various hardships to survival in a male dominated society. The Blue Room by Nafisa Rizvi vividly portrays the situation of women in patriarchal societies. Zaib and her aunt Zainab are consistently exploited by the male heads of their families. They never resist fulfilling their fixed gender roles. This research aims at finding out how women face and resist these situations in a lower class and bourgeoise family through a Marxist feminist interpretation of the novel at hand. The results of the study conclude that women are considered inferior to men in Pakistani conservative societies. The situation could be made better only if women could get proper education and empowerment. Keywords: Capitalist society, Male dominant society, The Blue Room, Marxist feminism